Does rural livelihood change? Household capital, climate shocks and farm entry-exit decisions in rural Pakistan - Ahmad, Muhammad Irshad; Oxley, Les; Ma, Hengyun; Liu, Ruifeng (Frontiers in Environmental Science, 2023)
Agriculture is a primary source of livelihoods in developing countries. The process of entry and exit of farming activities continues to play an important role in maintaining competition in agriculture and allocating resources between agriculture and other sectors. However, climate changes and other economic and social shocks have been severely affecting farmers’ livelihoods. This article examines rural household livelihood transition in the context of farm entry and exit decisions in rural Pakistan. Using 1867 rural household survey data, we brought insights into how livelihood assets, climate shocks, climate investment and locational characteristics affect their farm entry and exit decisions. The results indicate that the proportion of farm entry (24%) was higher than that of farm exit (15%). The major factors were crop inputs using as credit with a huge markup, crop inputs sold by farmers on net cash in financial crisis, climate shocks and poor climate investment that contributed to farm exit. They were household head characteristics, land ownership (family farm), and livestock ownership that increased the likelihood of farm entry decisions. Farm exit decisions were significantly and positively associated with household migration status, irrigation water shortage, off-farm income, crop input used as credit, crop diseases, climate shocks and lack of local government role in sharing climate knowledge. Furthermore, Propensity Score Matching (PSM) results found that the entry decision significantly decreases household income, while the exit decision significantly increases household income and food security status. These findings provide insights into farm entry and exit for those who are planning livelihood transition, and offer recommendations on how to overcome the constraints faced by farming businesses, agricultural sustainability, self-sufficiency and food security during the transition nationally and internationally.